ANSI (ANTI-HYPERTENSION) EXERCISE IS EFFECTIVE IN REDUCING BLOOD PRESSURE HYPERTENSION PATIENTS - Dwi Lina Octavia; widiharti; Ervi Suminar; Diah Jerita Eka Sari (Indonesian Journal of Community Health Nursing, 2025)
Introduction: Hypertension is a condition in which blood pressure in the blood vessels chronically increases. Apart from pharmacological therapy, management of hypertension uses non-pharmacological therapy such as ANSI (Anti Hypertension) exercises. This study aims to analyze the effect of ANSI (Anti Hypertension) exercise on blood pressure in hypertensive patients. Method: This research has a pre-experimental one group pre-post test design. Population of 107 hypertensive patients aged 56 - 65 years at the Industrial Health Center, Gresik District, Gresik Regency, East Java. A total of 44 hypertensive patients were included as samples based on a purposive sampling technique. The independent variable in this study is ANSI (Anti Hypertension) exercise and the dependent variable in this study is the blood pressure of hypertensive patients. The instruments used in this research were the Standard Operational Procedure (SOP) for ANSI (Anti Hypertension) exercise, a digital sphygmomanometer and a blood pressure observation sheet. The data was then analyzed using the Wilcoxon Signed Rank Test statistical test with a significance level of 95%. Result: Statistical test results showed that the reduction in systolic blood pressure after doing ANSI (Anti Hypertension) exercises was 5.41 mmHg, and diastolic blood pressure was 1.59 mmHg. The Wilcoxon Signed Rank Test statistical test has a p value = 0.00 (p value <0.05). Conclusion: ANSI (Anti Hypertension) exercise reduces systolic and diastolic blood pressure in hypertensive patients. Community nurses need to carry out educational activities and provide information on the importance of physical activity such as ANSI (Anti Hypertension) exercises in managing blood pressure. Community Health Centers need to provide policies by providing services and facilities to improve health programs, especially making ANSI (Anti Hypertension) exercise a routine program at least once a week, because it has many benefits for the health of hypertensive patients.